Organization of mobile learning as a new technology in education - Shulgina-Tarachshuk, A.S.; Turdybekova, K.M. (KSU Publ., 2018)
The article is devoted to the forms and methods of introducing mobile technologies into the educational process. The authors analyzed the advantages and disadvantages of mobile education. The definition of the concept of «mobile learning» as one of the key requirements for students is proposed, since computers and the Internet have become necessary educational tools, the technologies have become more portable, affordable, efficient and easy to use. In addition, the authors propose to familiarize themselves with the wide possibilities for expanding participation and access to ICT, in particular on the Internet. One of the main points to which special attention is paid is the introduction of tablet PCs, which makes it possible to use mobile Internet access with equal, if not more, functionality than desktop computers. The role of the student and the teacher in the process of performing independent work is singled out. It is noted that most mobile devices are useful in the field of education, management, organization and teaching for practitioners, as well as technical support tools for students.
Білім берудегі жаңа технологиялық мобильді оқытуды ұйымдастыру
Организация мобильного обучения как новая технология в образовании
Keywords: competence; initiative; innovativeness; mobility; flexibility; dynamism; contractibility; effective use of information technologies; ICT; m-learning